Peran Lingkungan dan Media Sosial Dalam Upaya Pencegahan Kenakalan Remaja di SMA Negeri 1 Ciranjang - Handyani, Trini; Amalia, Mia; Nur, Hilman; Mulyadi, M. Budi; Putri, Kayla Andini; Permana, Ajeng; Permatasari, Ira; Setiawan, Wandi (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service activity aims to increase the awareness of SMA Negeri 1 Ciranjang students towards the prevention of juvenile delinquency, especially bullying and sexual violence, through the role of the environment and social media. The method applied includes pre-test, material presentation by lecturers, panel discussion, and post-test. The material presented included the role of schools in building positive habits, sexual harassment prevention strategies, and strengthening the value of mutual cooperation as a form of tolerance in everyday life. The pre-test was used to measure students' initial level of understanding, while the post-test evaluated the increase in understanding after the activity. The results of the service show that students have a better understanding of the negative impact of juvenile delinquency and the importance of creating a safe environment at school. As many as 78.8% of students felt that this activity helped them understand issues related to bullying, sexual violence, and the wise use of social media. Supporting factors for the success of this program include full support from the school and the enthusiasm of the participants, while inhibiting factors include time constraints and a less conducive atmosphere. This activity is expected to provide students with insights on how to protect themselves from the threat of violence, understand the importance of tolerance, and increase awareness of the importance of maintaining local cultural values. Recommendations for future activities include developing more comprehensive materials and increasing participant engagement to create a more inclusive and safe school environment.